HAK ASASI MANUSIA DALAM KEBIJAKAN LUAR NEGERI INDONESIA - Sukendar, Sukendar (Universitas Serang Raya, 2015)
This paper discusses how Indonesia sees and interprets human rights, what distinguishes it from view of liberal democracy and how the implementation of human rights in Indonesia today. In the study it can be concluded that 1. The development seen today the implementation of a new human rights in Indonesia at this stage of the policy has not been part of the basic foundations of national life to be a factor of integration or union, 2. Today, in the Indonesia human rights diplomacy has several more steps advanced compared to some ASEAN countries, 3. at international level, Indonesia has also been a party to six of the seven top UN Covenant. These six major human rights convention is Covenant on Civil and Political Rights (ICCPR), International Covenant Ekososbud (ICESCR), the Convention Against Torture (CAT), Convention on the Rights of the Child (CRC), the Convention Penghapusam Discrimination against Women (CEDAW), the Convention on the Elimination of Racial Discrimination (CERD) Keyword: Human Rights, The Indonesian Foreign Policy